1992
DOI: 10.1111/j.1432-2277.1992.tb01763.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring antigenemia is useful in guiding treatment of severe cytomegalovirus disease after organ transplantation

Abstract: We investigated the value of monitoring CMV antigenemia during and after antiviral therapy for CMV disease. During the study period, 10 out of 214 renal transplant recipients were treated for CMV disease, receiving a total of 14 courses of treatment. Antigenemia decreased within 7 days after onset of treatment in eight of nine courses associated with a rapid clinical recovery. In three courses with a slow or absent response, antigenemia levels initially increased. Monitoring antigenemia was helpful in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Although CMV-PCR is a useful test for the diagnosis of CMV infection [13, 14, 15], many authors consider CMV-AG to be the best method for monitoring CMV infection and disease [16, 17, 18]. Tanabe et al [19]observed a good correlation between the results of CMV-AG and the clinical course of the disease in renal transplant recipients who where recovering from CMV disease after ganciclovir therapy.…”
Section: Discussionmentioning
confidence: 91%
“…Although CMV-PCR is a useful test for the diagnosis of CMV infection [13, 14, 15], many authors consider CMV-AG to be the best method for monitoring CMV infection and disease [16, 17, 18]. Tanabe et al [19]observed a good correlation between the results of CMV-AG and the clinical course of the disease in renal transplant recipients who where recovering from CMV disease after ganciclovir therapy.…”
Section: Discussionmentioning
confidence: 91%